Toward an interactive Voronoi Treemap for manual arrangement and grouping - Abuthawabeh, Ala; Aupetit, Michaël (EuroVis 2021: Short Paper Proceedings of the EG Conference on Visualization, 2021)
Interactive spatial arrangement and grouping (A&G) of images is a critical step of the sense-making process. We argue that to support A&G tasks, a visual encoding idiom should avoid clutter, show groups explicitly, and maximize the use of space while allowing free positioning. None of the existing interactive idioms supporting A&G tasks optimizes all these criteria at once. We propose and implement an interactive Voronoi treemap for A&G that fulfills all these requirements. The cells representing groups or objects can be dragged or clicked to arrange objects and groups and to create, merge, split, expand, or collapse groups. We present a usage scenario for an art quiz game and a comparative analysis of our approach to the recent Piling.js library for a categorization task of HiC data images. We discuss limitations and future work.